Implementation of Character Education in Developing Religious Personality Among Students at Sekolah Rendah Al-Amin Gombak, Kuala Lumpur-Malaysia - Zulhammi Zulhammi; Zulhimma Zulhimma; Zainal Hasibuan; Mohd Syahil bin Mohd Rawi; Fahrina Yustiasari Liriwati; Sy’adatun Nikmah; Fauzan Hamidi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the implementation of character education to develop a religious personality among students at Sekolah Rendah Al-Amin Gombak, Kuala Lumpur. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings indicate that character education at the school is integrated into academic subjects, daily routines, and school culture. Teachers and school leaders play significant roles as moral exemplars. The study concludes that a consistent, religious-based school environment promotes the internalization of Islamic values and behaviors among students, reinforcing their religious identity and character.